A behavioral finance model of the exchange rate with many forecasting rules - Paul De Grauwe; Pablo Rovira Kaltwasser (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper presents a behavioral finance model of the exchange rate. Agents forecast the exchange rate by means of very simple rules. They can choose between three groups of forecasting rules: fundamentalist, extrapolative and momentum rules. Agents using a fundamentalist rule are not able to observe the true value of the fundamental exchange and therefore have to rely on an estimate of this variable to make a forecast. Based on simulation analysis we find that two types of equilibria exist, a fundamental and a non-fundamental one. Both the probability of finding a particular type of equilibrium and the probability of switching between different types of equilibria depend on the number of rules available to agents. Furthermore, we find that the exchange rate dynamics is sensitive to initial conditions and to the risk perception about the underlying fundamental. Both results are dependent on the number of forecasting rules.
Keywords: F31; C53; 330